2013
DOI: 10.1016/j.otsr.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postoperative outcome for acetabular fractures

Abstract: Poor reduction, associated injuries, fracture displacement of >20mm, joint dislocation and late surgery definitely carry poor prognosis in predicting the outcome of surgically treated acetabular fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 18 publications
6
66
4
2
Order By: Relevance
“…In our series, we showed a conversion rate of 6% after 10 years of FU. For operatively treated fractures the rate of secondary THA is higher, with reported rates between 8 % and 53% 41,42,57,73,119,136,154 . Our cohort of operatively treated fractures had a conversion rate to THA of 14% after an average FU of 11 years.…”
Section: Secondary Total Hip Replacementmentioning
confidence: 99%
“…In our series, we showed a conversion rate of 6% after 10 years of FU. For operatively treated fractures the rate of secondary THA is higher, with reported rates between 8 % and 53% 41,42,57,73,119,136,154 . Our cohort of operatively treated fractures had a conversion rate to THA of 14% after an average FU of 11 years.…”
Section: Secondary Total Hip Replacementmentioning
confidence: 99%
“…Clinical outcome has been reported to decrease with increasing patient age [8, 9], while other researchers could not confirm these findings [10–12]. Fracture pattern is often [8, 13, 14] but not necessarily [11] considered as a significant predictor of radiographic and functional results. However, gender is not supposed to influence the outcome after acetabular surgery [11, 12, 15], whereas early ORIF can be assumed to result in a higher likelihood of excellent or good radiographic results [8, 13, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Good results are, however, closely associated with the fracture reduction, and a residual step-off over 2-3 mm will lead to significantly reduced hip joint survival and clinical results. It is suggested that approximately 11-19% of the acetabular fracture patients will develop symptomatic arthritis [8,[23][24][25] and 6% -11% will eventually receive a total hip arthroplasty (THA) [8,[23][24][25]. The reported results of delayed THA after operatively treated acetabular fractures vary widely as do the type of arthroplasties performed.…”
Section: Introductionmentioning
confidence: 99%